STUDI LITERATUR: DAMPAK PENGGUNAAN MEDIA SOSIAL TERHADAP PRESTASI BELAJAR SISWA KELAS TINGGI DI SEKOLAH DASAR - Kamila, Kamila Syifa Maulida; Endang M Kurnianti; Susi Winarni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of social media use on the academic achievement of upper-grade elementary school students. The method employed is a literature review, gathering data from books, articles, scholarly journals, and other primary statistical sources. The analysis process proceeds through three stages: grouping relevant literature, summarizing the data into a unified whole, and examining key information within each source. The findings indicate that students’ use of social media exerts both positive and negative effects on their learning outcomes. On the positive side, social media can serve as a learning tool, an information resource, and a means to develop students’ creativity and academic skills. Conversely, the negative impacts include disruptions to concentration, decreased motivation to study, dependence on gadgets, and exposure to age-inappropriate content. To minimize these adverse effects, active involvement from parents and teachers is required to monitor and guide social media use responsibly. With proper supervision, social media can become an effective educational support for elementary school students.